Nelson Mandela - Kramer, Barbara (Washington, D.C. : National Geographic, 2014)
"Nelson Mandela, who courageously dealt with adversity and emerged a world leader, has been an inspirational role model for millions of people around the world, from students to presidents. After being imprisoned for 27 years, in 1994 he became South Africa's first democratically-elected president and shared the Nobel Peace Prize. Mandela died in 2013, but his legacy lives on as a barrier-breaker and humanitarian. Learn all about his life, especially the challenges he faced and how he persevered, in this thoughtful biography."--
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Description based on print version record.
Keywords: Mandela, Nelson, -- 1918-2013 -- Juvenile literature; Presidents -- South Africa -- Biography -- Juvenile literature; Anti-apartheid activists -- South Africa -- Biography -- Juvenile literature; Political prisoners -- South Africa -- Biography -- Juvenile literature; Anti-apartheid movements -- South Africa -- Juvenile literature; South Africa -- Politics and government -- 1948-1994 -- Juvenile literature; South Africa -- Politics and government -- 1994- -- Juvenile literature; Electronic books- OSLIS; Electronic books